Erase The Disciplinary Penalty as A Guarantee For Employees to Remove its Effects - Kadhim, Sarmad Jawad (Indonesian Journal of Law and Economics Review, 2023)
This scientific article presents a comparative analysis of the erasure of disciplinary penalties for public employees in the context of organizational and statutory relationships with the state. The study explores the historical evolution of terminology used in Iraqi legislation, transitioning from "nullification" to "cancellation" in recent years. Despite variations in nomenclature, the essence of erasure remains consistent across legislations. Notably, the researched laws do not offer a legislative definition of erasure, relying instead on legal texts to regulate its application. Furthermore, the study highlights the role of administrative judiciary in handling erasure cases without providing a specific definition. By examining the goals, methods, and implications of erasure provisions, this research contributes valuable insights to the field of public employment law, aiming to foster stability in public utilities and ensure the efficient functioning of public services. Highlights: Historical evolution of terminology in Iraqi legislation. Lack of a legislative definition for erasure in researched laws. Role of administrative judiciary in handling erasure cases. Keywords: Erasure, Disciplinary Penalties, Public Employees, Organizational Relationships, Statutory Relationships